RANCANG BANGUN SISTEM INFORMASI POSYANDU BERBASIS WEB PADA POSYANDU MAWAR MERAH KELURAHAN KEDAUNG - Arju Zumaro Fahmi; Nardiono (CV. Multi Kreasi Media, 2024)
Posyandu Mawar Merah has the duty to carry out health service activities for pregnant women, children and the elderly. In carrying out data processing, Posyandu cadres often experience difficulties in the process of writing reports and searching for data because the data is still handwritten, making it difficult for other cadres to find the data. The Mawar Merah Posyandu does not yet have a web-based Posyandu Information System, so it is still experiencing difficulties in searching Posyandu participant data, and the large number of applicants also makes it difficult to process and re-access data because a lot of the same data must be recorded repeatedly into different forms. -different, causing the occurrence of similarity of data. This study aims to facilitate the task of Posyandu cadres in processing Posyandu participant data. The method used in the research is Waterfall. In building this system the tools used are PHP as a programming language. XAMPP as a web server and MySQL as a database. The results of this research are in the form of a Web-Based Posyandu Information System. This system has been tested with a 100% success rate so that it can make it easier for users to search and process data on Posyandu participants.